ANALYZING LOCAL MICRO BUSINESSES SURVIVAL STRATEGIES DURING CORONA VIRUS PANDEMIC IN MANADO - Pangow, Laurel F. E.; Kindangen, Paulus; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2021)
The phenomenon of the Covid-19 pandemic that occurred in Indonesia not only had an impact on the health sector but also had an impact on the country's economy. Indonesia, which is dominated by micro-enterprises, needs to pay special attention to this sector because the contribution of micro-enterprises to the national economy is quite large. The study aims to find out micro businesses survival strategies and its implementation during the corona virus pandemic. To find out the strategies and the implementations, the researcher uses the perspective, position, and plan as indicators in this study. This study uses a qualitative method with purposive sampling through in-depth interviews. This study conducted interviews with 15 businesses that classified as micro business. The findings of this study indicate that most of the informants use social media by showing the products or services, show how is the packaging of the products, giving discount, giveaway promotion, and also cooperate with online delivery providers to deliver products in order to survive during the pandemic. Informants will also continue to rely on these strategies to bounce back from crisis situation. From the results of research, it is recommended for the Government, micro businesses in Manado and future research purposes.Â Keywords: micro business, pandemic, corona virus, survival strategies, perspective, position, plan